Isolation and Characterization of Lactic Acid Bacteria (Lactobacillus sp) from Tomato (Solanum lycopersicum) - Resti Fevria; Indra Hartanto (UNIVERSITAS NEGERI PADANG, 2018)
Prebiotics are good coumpounds used in the growth of lactic acid bacteria (LAB) in digestion, prebiotics come from vegetables, fruits and seeds. Tomatoes are thought to be one of the natural media of bacteria because tomatoes contain various chemical compositions that are needed as a substrate for LAB. The purpose of this study is to isolate and determine the type of LAB produced microscopically. The ingredients used are tomatoes obtained from Padang Panjang market, with Merck NA media, oxoid MRSa, 0,9% NaCl, and crystal violet paint. Isolation LAB from tomatoes done in two ways, the first with plant tomato tissue directly into the NA medium and the second with fermentation tomato and then plant the tomato into the MRSa medium with streak plate methods. The isolates obtained were identified microscopically using a microscope with gram staining method. From the research that has been done, the following result are obtained : (1) Plant tomatoes tissue direcly into NA medium and gram staining, there were 1 colonies of gram positive bacteria with bacil cell form. (2). Fermentation tomatoes from the results, there were 2 colonies gram positive bacteria with bacil cell form. We can identify this colonies as Lactobacillius bulgaricus.